2015
DOI: 10.1103/physrevd.92.103510
|View full text |Cite
|
Sign up to set email alerts
|

Theory of dark matter superfluidity

Abstract: We propose a novel theory of dark matter (DM) superfluidity that matches the successes of the ΛCDM model on cosmological scales while simultaneously reproducing the MOdified Newtonian Dynamics (MOND) phenomenology on galactic scales. The DM and MOND components have a common origin, representing different phases of a single underlying substance. DM consists of axion-like particles with mass of order eV and strong self-interactions. The condensate has a polytropic equation of state P ∼ ρ 3 giving rise to a super… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
605
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(647 citation statements)
references
References 247 publications
(426 reference statements)
18
605
5
Order By: Relevance
“…GCs with a weak external field and extended velocity dispersion profiles, such as NGC 2419, display similar tensions (Ibata et al 2011), but see also Gentile et al (2010) and Sanders (2012). Note however that, in theories like those of Berezhiani & Khoury (2015), such tensions would be expected since MOND would only be an effective description of gravity within a given distance from the host galaxy (∼100 kpc in the case of the MW). However, clusters which are closer to the Galactic center and dominated by the external gravitational field of the MW are also interesting as long as the external field is below a 0 .…”
Section: Mondmentioning
confidence: 98%
See 1 more Smart Citation
“…GCs with a weak external field and extended velocity dispersion profiles, such as NGC 2419, display similar tensions (Ibata et al 2011), but see also Gentile et al (2010) and Sanders (2012). Note however that, in theories like those of Berezhiani & Khoury (2015), such tensions would be expected since MOND would only be an effective description of gravity within a given distance from the host galaxy (∼100 kpc in the case of the MW). However, clusters which are closer to the Galactic center and dominated by the external gravitational field of the MW are also interesting as long as the external field is below a 0 .…”
Section: Mondmentioning
confidence: 98%
“…This could mean that it is either an effective way to predict how dark matter (DM) is arranged in galaxies, or that it is an effective modification of gravity resulting from a broader theory of the dark sector (e.g. Blanchet & Heisenberg 2015;Berezhiani & Khoury 2015). To distinguish between these possibilities, it is absolutely mandatory to check for distinctive predictions of this paradigm in its a priori domain of validity, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…For example it is interesting to note that the strange-seeming power of 2/3 in the Lagrangian was also used in [13]. In [13], the authors showed that a superfluid with this type of Lagrangian can reproduce MOND-like behavior in the superfluid phase.…”
Section: Learning From the Lagrangianmentioning
confidence: 99%
“…For example it is interesting to note that the strange-seeming power of 2/3 in the Lagrangian was also used in [13]. In [13], the authors showed that a superfluid with this type of Lagrangian can reproduce MOND-like behavior in the superfluid phase. But -much like Verlinde's emergent gravity -has the benefit of displaying a different behavior on short distances, where a large gradient near sources of high energydensity (like, eg, stars) renders the superfluid approximation invalid.…”
Section: Learning From the Lagrangianmentioning
confidence: 99%
“…But this scenario is also not free from observational challenges as the recently measured abundance of ultrafaint lensed galaxies at z ≃ 6 in the Hubble Frontier Fields might provide stringent constraints on the success of ULA dark matter in explaining dSph cores [23]. Another dark matter candidate, which was proposed very recently [24], claims to solve the corecusp issue at small scales due to the superfluidic effect of the scalar-dark matter condensate at the small scale while replicating the success of CDM at the large scale.…”
Section: Introductionmentioning
confidence: 99%